2017
DOI: 10.3928/01477447-20161128-02
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Exposure and Rotator Cuff Repair in a Rat Model

Abstract: Simvastatin is a common medication prescribed for hypercholesterolemia that accelerates local bone formation. It is unclear whether simvastatin can accelerate healing at the tendon-bone interface after rotator cuff repair. This study was conducted to investigate whether local and systemic administration of simvastatin increased tendon-bone healing of the rotator cuff as detected by maximum load to failure in a controlled animal-based model. Supraspinatus tendon repair was performed on 120 Sprague-Dawley rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…7,11,27 Dolkart et al 14 studied 48 healthy (non-hyperlipidemic) rats and found enhanced biomechanical properties (maximal load to repair failure and stiffness) of repaired cuff tendon in statintreated rats compared to saline-treated rats (P < 0.001). In contrast, Deren et al, 13 in their study of 80 healthy (non-hyperlipidemic) rats, found similar strength (maximum load to repair failure) and histology (collagen organization, cellularity, vascularity, cartilage formation, new bony matrix deposition) at the tendon-bone healing site in rats treated with local or systemic statin versus non-treated rats (P > 0.05). The results of these contradictory studies make it difficult to draw firm conclusions regarding the effect of statin.…”
Section: Level Of Evidencementioning
confidence: 86%
“…7,11,27 Dolkart et al 14 studied 48 healthy (non-hyperlipidemic) rats and found enhanced biomechanical properties (maximal load to repair failure and stiffness) of repaired cuff tendon in statintreated rats compared to saline-treated rats (P < 0.001). In contrast, Deren et al, 13 in their study of 80 healthy (non-hyperlipidemic) rats, found similar strength (maximum load to repair failure) and histology (collagen organization, cellularity, vascularity, cartilage formation, new bony matrix deposition) at the tendon-bone healing site in rats treated with local or systemic statin versus non-treated rats (P > 0.05). The results of these contradictory studies make it difficult to draw firm conclusions regarding the effect of statin.…”
Section: Level Of Evidencementioning
confidence: 86%
“…Differences in revascularization, collagenization, and inflammatory cell infiltration were also observed histologically, but did not reach statistical significance. Deren et al 26 showed that locally used simvastatin-loaded polylactic acid membrane or oral administration of simvastatin were not beneficial to healing after rotator cuff repair. Eliasson et al 25 conducted an in vitro cell culture experiment, showing that simvastatin and atorvastatin decreased the cell proliferation and mechanical strength of the tendon construct.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of statins on the healing after rotator cuff repair was widely explored [ 11 , 17 ]. Muscle atrophy, fibrosis, and fatty infiltration of the supraspinatus muscle usually occurred following rotator cuff tears.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have showed positive effects of statin use on the healing after rotator cuff repair, different results have been reported. Deren et al [ 11 ] investigated whether local and systemic administration of simvastatin increased tendon-bone healing in a rat rotator cuff repair model and indicated that the use of systemic and local simvastatin offered no benefit. In addition, Garcia et al [ 26 ] showed that type and dosage of statin medication did not significantly affect the incidence of retear after rotator cuff repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation